The Influence of Search Engines and Generative AI on Trust, Satisfaction, and Purchase Intention: An Experimental Study - Roswinanto, Widyarso; Maulani, Heidi (Jurnal Ilmu Manajemen dan Ekonomika, 2025)
This study examines the effects of digital information search media (search engines versus generative AI) and product type (goods versus services) on consumer responses. Using a 2 × 2 factorial experimental design and ANCOVA analysis, data were collected from 146 respondents aged 20–40 years. The variables measured include trust, satisfaction, and purchase intention. The results show that media type has no significant effect on dependent variables, while product type significantly influences trust and satisfaction but not purchase intention. A significant interaction effect between media type and product type is found for trust and satisfaction, indicating that generative AI is preferred for goods, whereas both media perform similarly for services.